Anthropometry and performance characteristics of recreational advanced to elite female rock climbers - Giles, D.; Barnes, K.; Taylor, N.; Chidley, C.; Chidley, J.; Mitchell, J.; Gibson-Smith, E.; España-Romero, V. (Journal of Sports Sciences, 2020)
Despite climbing`s popularity and an increasing number of female participants, there are limited anthropometric and performance data for this population. This study compares the characteristics of 55 experienced female climbers, divided into three categories (lower [ADV-L] and higher advanced [ADV-H] and elite [ELT]) based on self-reported ability. Data on climbing experience, body dimensions, body composition, flexibility, lower and upper-body power and finger strength were assessed. ELT climbers differed significantly from the ADV groups in age (Mean Difference [MD] = 8.8-9.8 yrs; despite smaller differences in years climbing MD = 1.6-2.4 yrs), greater climbing and hours training per week (MD = 3.0-3.7 h & MD = 0.9-1.6 h, respectively), and greater upper-body power (MD = 12.9-16.6 cm) and finger strength (MD = 51.6-65.4 N). Linear regression analysis showed finger strength and upper body power to be associated with ability, particularly when adjusting for descriptive and anthropometric variables (finger strength R2 = 53% and 45%; upper-body power R2 = 60% and 39% for boulder and sport, respectively). The findings support the importance of finger strength and upper-body power; changes in female anthropometric data over the last decade provide insight into the changing nature of the sport.